Expression of the HPV16E7 Oncoprotein by Thymic Epithelium is Accompanied by Disrupted T Cell Maturation and a Failure of the Thymus to Involute with Age. Issue 2 (2003) - Malcolm, K. M.; Gill, J.; Leggatt, G. R.; Boyd, R.; Lambert, P.; Frazer, I. H.
Abstract : Transgenic mice expressing the E7 protein of HPV16 from the keratin 14 promoter demonstrate increasing thymic hypertrophy with age. This hypertrophy is associated with increased absolute numbers of all thymocyte types, and with increased cortical and medullary cellularity. In the thymic medulla, increased compartmentalization of the major thymic stromal cell types and expansion of thymic epithelial cell population is observed. Neither an increased rate of immature thymocyte division nor a decreased rate of immature thymocyte death was able to account for the observed hypertrophy. Thymocytes with reduced levels of expression of CD4 and/or CD8 were more abundant in transgenic (tg) mice and became increasingly more so with age. These thymic SP and DP populations with reduced levels of CD4 and/or CD8 markers had a lower rate of apoptosis in the tg than in the non-tg mice. The rate of export of mature thymocytes to peripheral lymphoid organs was less in tg animals relative to the pool of available mature cells, particularly for the increasingly abundant CD4 lo population. We therefore suggest that mature thymocytes that would normally die in the thymus gradually accumulated in E7 transgenic animals, perhaps as a consequence of exposure to a hypertrophied E7-expressing thymic epithelium or to factors secreted by this expanded thymic stromal cell population. The K14E7 transgenic mouse thus provides a unique model to study effects of the thymic epithelial cell compartment on thymus development and involution.